Understanding Vietnamese consumers’ perception and word-of-mouth intentions towards Airbnb - Do, Thuc (2023)
PurposeThis paper aims to provide a comprehensive understanding of Vietnamese consumers' perceived value and to explore the relationships between its constructs, satisfaction and (e)word-of-mouth (WOM) intentions towards Airbnb. Moreover, the relationship between traditional WOM and electronic WOM (eWOM) was also investigated. Design/methodology/approachAn electronic survey was applied to collect data on a sample of Vietnamese Airbnb guests. A total of 352 questionnaires were collected, from which 163 eligible Airbnb users remained for data analysis. The partial least square approach to structural equation modelling was used to analyse the data. FindingsThe findings suggested that monetary, functional and hedonic benefits significantly impact Vietnamese customer satisfaction (CS) with Airbnb accommodation, which, in turn, acts as a direct effect and mediator in encouraging customers' (e)WOM-giving intentions. Moreover, traditional WOM intention positively influences eWOM giving intention. Originality/valueThis study provides a better comprehension of customers' perceived value that influences CS and their (e)WOM intentions towards Airbnb. Secondly, it extends the literature on WOM intentions from the message communicator's perspective by confirming the positive association between traditional and eWOM-giving intentions. Finally, this paper reveals insights into the sharing accommodation in a fast-growing market in South East Asia (Vietnam), which supports sharing accommodation platforms and service providers to develop appropriate marketing strategies.